Constraints, Contradictions and Challenges regarding Cooperation of Parents during COVID-19: A Social Capital Perspective - Motsumi Tshegofatso Portia; Khumalo Shuti Steph (Sciendo, 2024)
When calamity hits humanity in the form of natural disasters, they appear unannounced. The same applies to the recent destructive and disruptive Covid-19 pandemic. During the early days of this pandemic, life activities were halted abruptly. Global education systems were not spared - most institutions were caught napping and forced to close. The educational development of children was adversely affected by the hard lockdown and stringent restrictions that followed the outbreak of the pandemic. The role that parents had to play in the education of their children needed to evolve to meet the new demands.